The Relationship Between Self-Compassion and Loneliness in Adolescents - Endang Rifani; Syifaul Ummah; Yusuf Hasan Baharudin; Dewi Lestari; Aliu Adedayo Adediran (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2024)
Self-compassion refers to an individual's ability to acknowledge, endure, and find value in challenging experiences, such as the hardship of living far away from one's parents and family. The prevailing sentiment of solitude is currently being experienced by a majority of youth, students, workers, and other individuals. The objective of this study is to establish the correlation between self-compassion and loneliness. This study employed a quantitative correlational research design. The data collection strategy employed two scales, namely the Self-Compassion Scale (SCS) and the R-UCLA Loneliness Scale. Data collection was conducted by utilizing Google forms, which were disseminated to the research participants. This study encompassed a cohort of 122 teenagers, comprising high school students, university students, and workers. The data analysis using descriptive analytic methodologies. The study findings indicate that the degree of self-compassion towards loneliness falls within the moderate range. The article contains a detailed analysis and final thoughts on this matter.